Os limites do consentimento fornecido pelo consumidor nos contratos de adesão para a comercialização de seus dados pessoais: uma análise à luz da Lei 13.709/2018 - Freitas, Bruno Dias de (2021)
The present work deals with the limits of consumer consent to supply of your personal data, to be marketed/transferred, under the contracts membership. For this, an analysis of the evolution that the consumer market has undergone in the recent centuries (from the perspective of freedom to contract vs. contractual freedom), evidencing the need for the emergence of a dynamic contractual instrument, namely the contracts of accession. Pervades the abusiveness of the contractual clauses contained in this modality contractual, aiming to demonstrate the normative protection existing before the LGPD. demonstrates, from concrete cases, the need for the emergence of specific legislation that protect the protection of personal data. From this analysis, the basics existing legal frameworks in the LGPD and how they are applied in practical cases, in particular the legal basis of the consent. A dialogue is also held on how the LGPD protects marketing and processing of personal data. From there, it is possible to verify the invalidity of data treatments in the form commonly promoted by companies, supported on the legal basis of consent, when this is provided in an adhesion contract, as certainly not free, unambiguous and specific